2020
DOI: 10.4314/ahs.v20i2.52
|View full text |Cite
|
Sign up to set email alerts
|

Five years after commencing the objective structured clinical examination: are we getting it right? Medical students’ assessment as the measuring index

Abstract: Introduction: The aim of this study was to assess our use of OSCE from the perception of final year medical students. Materials and methods: This is a cross sectional survey of final year medical students undergoing the final examination in Surgery. All 102 medical students in the class were given the self-administered questionnaire to fill. The data were collated into excel spreadsheets and analysed using the SPSS version 21. Results: A total of 79 completed questionnaires were retrieved (return r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…Regarding the attributes of OSCE, nearly half of the students agreed that the OSCE was fairly designed, and a greater proportion believed that a wide range of skills had been included, which was in line with other studies (15,16,17) .In contrast, numerous studies have revealed a greater positive perception of the students towards attributes of OSCE (8,(18)(19)(20)(21) .Meanwhile, only one-third of the students agreed that the OSCE could minimise their chance of failing; This was expected, as it was their first time performing this assessment. Similar results were found in a study in Jamaica, in which less than a third of the examinees perceived that the OSCE minimalised the chance of failing (11) .…”
Section: Student's Perception Of Oscesupporting
confidence: 85%
See 1 more Smart Citation
“…Regarding the attributes of OSCE, nearly half of the students agreed that the OSCE was fairly designed, and a greater proportion believed that a wide range of skills had been included, which was in line with other studies (15,16,17) .In contrast, numerous studies have revealed a greater positive perception of the students towards attributes of OSCE (8,(18)(19)(20)(21) .Meanwhile, only one-third of the students agreed that the OSCE could minimise their chance of failing; This was expected, as it was their first time performing this assessment. Similar results were found in a study in Jamaica, in which less than a third of the examinees perceived that the OSCE minimalised the chance of failing (11) .…”
Section: Student's Perception Of Oscesupporting
confidence: 85%
“…Few students believed that simulators were needed in the following stations; basic life support, chest tube insertion, and nasogastric tube insertion. The performance of such skills with the presence of simulators may improve students' perception and decrease variability (31) .Nonetheless, it is costly to provide mannequins in 5 places with 2 circuit stations; alternatively, revising the requested skills and replacing them with the ones that can be tried on a trained patient is more logical (32) .Although few students suggested the assessor should be more helpful, their concern should be considered as the examiner's attitude can affect a student's performance (19,20,32) .…”
Section: Student's Perception Of Oscementioning
confidence: 99%
“…The case vignette and task descriptions of the stations were clear and distinct, which is often described by other studies but may be biased by the one-sided publication of good results ( 40–43 ). A total of 78% of the respondents prefer an OSCE, corresponding to studies in Ethiopia and Nigeria ( 44 , 45 ). A reason for this may be that the students find the OSCE less difficult than written examinations, although this stands in contrast to the fact that published OSCE results show a wide range, some with better and some with worse results in comparison to written assessment ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%